1969
DOI: 10.1128/aem.18.4.535-541.1969
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Media for the Isolation of Common Bacterial L-Phase Organisms from a Clinical Specimen

Abstract: The L-phase of 13 bacteria commonly associated with disease were induced by penicillin and inoculated into various solid and broth media; their growth was recorded for a period of 14 days. Plates containing highly purified agar and sucrose as the stabilizing agent and those incubated under aerobic conditions gave the best results. Magnesium seems to be necessary for growth in broth media on primary isolation, although it may not be necessary on multiple transfers after a more stable state has been reached. Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1976
1976
2001
2001

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…In no case did aerobic incubation increase the induction frequency. These findings conflict with the reports that anaerobic conditions do not benefit the growth of CWD bacteria (9,10,11,13). This disagreement probably stems from other investigators selecting species or strains with a propensity for producing aerobic CWD forms or fortuitously choosing an organism with the qualities of our group I organisms.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In no case did aerobic incubation increase the induction frequency. These findings conflict with the reports that anaerobic conditions do not benefit the growth of CWD bacteria (9,10,11,13). This disagreement probably stems from other investigators selecting species or strains with a propensity for producing aerobic CWD forms or fortuitously choosing an organism with the qualities of our group I organisms.…”
Section: Discussioncontrasting
confidence: 61%
“…Landman et al (9) obtained a quantitative conversion of Proteus mirabilis and Escherichia coli to L-forms with aerobic incubation. Nimmo and Blazevic (13) reported that the growth rate of previously induced L-forms of E. coli was greater with aerobic incubation. Lederberg and St. Clair (11) reported strain variation in the ability of E. coli to grow as L-form colonies but found no special atmosphere necessary for L-type growth.…”
mentioning
confidence: 99%